Language and Cultural Issues for English-as-a-Second/Foreign Language Students in Transnational Educational Settings - Briguglio, Carmela (Routledge, 2000)
As transnational education continues to expand, providing countries are becoming increasingly aware of the need to offer a high-quality ''product'' in all aspects. Such provision includes not only the offering of quality courses but also the provision of the support structures that international students require. In many cases, the educational ''package'' is delivered in the English language that for many students is a second or foreign language. While the status of English as a ''world language'' makes it highly desirable to earn a higher degree in that language, the linguistic and cultural difficulties that doing so poses for many students should not be underestimated. This article discusses issues of educational support for international students and offers some suggestions based on the findings of several research projects undertaken in recent years at the Curtin University of Technology.